Modul Enam Sasaran Keselamatan Pasien dalam Pembelajaran Klinik terhadap Perilaku Mahasiswa Keperawatan - Efitra Efitra; Reflita Reflita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effectiveness of module 6 patient safety goals in clinical learning on behavioral changes in nursing students at RSAM Bukittinggi. This research is a quasi-experimental research with a pretest-posttest control group design. The results showed that the control group obtained an average of 23 and 28.40 in the treatment group. Attitudes received an average of 51.27 in the control group and 59.6 in the treatment group. Furthermore, the action obtained an average of 28.93 in the control group and 39.6 in the treatment group. Behavioral analysis showed a p-value <0.05. In conclusion, module 6 patient safety goals effectively increase knowledge and actions or implement patient safety goals. Keywords: Module 6 Patient Safety Goals, Clinical Learning